Effect of investor fear on Australian financial markets - Smales, Lee (Routledge, 2017)
We examine the relationship between changes in the level of investor fear (proxied by the ASX 200 implied volatility index) and Australian financial market returns. We document a statistically significant relationship, across asset classes, where returns decline as investor fear increases. Returns are more sensitive to changes in the level of investor fear during the financial crisis of 2008–2009, when investor fear spikes sharply. Taken together, the results confirm that Australian financial market returns are closely related to prevailing levels of investor fear.